Impact of therapeutic hypothermia on infantile spasms: an observational cohort study. (13th September 2019) - Abu Dhais, Farah; McNamara, Brian; O'Mahony, Olivia; McSweeney, Niamh; Livingstone, Vicki; Murray, Deirdre M; Boylan, Geraldine B
Abstract : Aim: To establish the incidence of infantile spasms in children in the southern region of the Republic of Ireland and to compare the incidence of infantile spasms before and after the introduction of therapeutic hypothermia in infants with hypoxic‐ischemic encephalopathy (HIE). Method: Children born between 2003 and 2015 and diagnosed with infantile spasms (epileptic spasms with or without hypsarrhythmia) in the first 2 years of life were identified through audits of electroencephalography reports and paediatric neurology patient lists. Data on live births were obtained from the regional hospital statistics databases. Medical charts of infantile spasm cases were reviewed for demographic information, diagnostic workup results, treatment response, disease course, and developmental outcome. Results: Forty‐two infants with infantile spasms were identified. The cumulative incidence of infantile spasms up to the age of 2 years was 4.01 per 10 000 live births. Difference due to sex was minimal (22 males, 20 females) and most infants were delivered at or near term with gestational ages ranging between 30.0 and 41.8 weeks (median [interquartile range] 39.6wks [38.1–40.0wks]). The aetiology for infantile spasms was identified in almost two‐thirds of cases, with HIE being the single most common cause ( n =7). Other causes included chromosomal and monogenetic abnormalities ( n =8). Infantile spasms occurred in moderate and severe grades of HIE, with a significantly higher incidence in those with severe HIE ( p =0.029). Infants with severe HIE who did not receive therapeutic hypothermia were six times more likely to develop infantile spasms compared to those who did, but the difference was not statistically significant (4 out of 16 vs 1 out of 24, p =0.138). Interpretation: This study provides detailed information about infantile spasms before and after the introduction of therapeutic hypothermia. HIE severity is a risk factor for the development of infantile spasms. The introduction of therapeutic hypothermia may have had an impact, but the effect was hard to ascertain in this cohort due to the small number of infants. What this paper adds: The incidence of infantile spasms and patient characteristics in the southern region of the Republic of Ireland is similar to internationally published data. None of the infants with a history of mild hypoxic‐ischemic encephalopathy (HIE) developed infantile spasms. The risk of infantile spasms was higher in infants with severe HIE. Infantile spasms were more frequent in infants with severe HIE not treated with therapeutic hypothermia. What this paper adds: The incidence of infantile spasms and patient characteristics in the southern region of the Republic of Ireland is similar to internationally published data. None of the infants with a history of mild hypoxic‐ischemic encephalopathy (HIE) developed infantile spasms. The risk of infantile spasms was higher in infants with severe HIE. Infantile spasms were more frequent in infants with severe HIE not treated with therapeutic hypothermia. This article's abstract has been translated into Spanish and Portuguese. Follow the links from the abstract to view the translations. This article is commented on by Vollmer on page 9 of this issue. Resumen: Impacto de la hipotermia como tratamiento en los espasmos infantiles: un estudio de cohorte observacional: Objetivo: Establecer la incidencia de los espasmos infantiles en niños de la República de Irlanda y comparar la incidencia de los espasmos infantiles antes y después de la introducción de la hipotermia terapéutica en niños con encefalopatía hipóxico‐isquémica (EHI). Método: Niños nacidos entre 2003 y 2015 y diagnosticados con espasmos infantiles (espasmos epilépticos con o sin hipsarritmia) en los primeros 2 años de vida fueron identificados por medio de auditorías de reportes de electroencefalográficos y listas de pacientes de neurólogos infantiles. Datos sobre los nacidos vivos se obtuvieron de la base de datos estadística del hospital regional. Las historias clínicas de los casos de espasmos infantiles fueron revisadas para obtener datos demográficos, resultados diagnósticos, respuesta a tratamiento, curso de la enfermedad y resultados del desarrollo. Resultados: Fueron identificados 42 niños con espasmos infantiles. La incidencia acumulada de los espasmos infantiles por encima de los 2 años fue de 4, 01 por 10.000 nacidos vivos. La diferencia debida al sexo fue mínima (22 masculinos, 20 femeninos) y la mayoría nacieron en o cercano a término, con edad gestacional entre 30, 0 y 41, 8 semanas (media (rango Intercuartil) 39, 6 semanas (38, 1‐40, 0 semanas). La etiología de espasmos infantiles fue identificada en dos tercios de los casos, siendo EHI la causa más común (7 de 42). Otras causas incluyeron anormalidades cromosómicas y monogénicas (8 de 42). Los espasmos infantiles ocurrieron en los grados moderados y severos de EHI con incidencia significativamente mayor en aquellos casos severos de EHI (p=0, 029). Los niños con EHI severo que no recibieron hipotermia terapéutica tuvieron una probabilidad seis veces mayor de desarrollar espasmos infantiles comparados con aquellos quienes la recibieron, pero la diferencia no era estadísticamente significativa (4 de 16 vs 1 de 14, p=0, 138). Interpretación: Este estudio proporciona información detallada acerca de los espasmos infantiles antes y después de la introducción de la hipotermia terapéutica. La severidad de la EHI es un factor de riesgo para el desarrollo de los espasmos infantiles. La introducción de la hipotermia terapéutica puede haber tenido un impacto, pero el efecto fue difícil de determinar en esta cohorte debido al pequeño número de recién nacidos. Resumo: Impacto da hipotermia terapêutica nos espasmos infantis: um estudo de coorte observacional: Objetivo: Estabelecer a incidência de espasmos infantis em crianças da República da Irlanda e comparar a incidência de espasmos infantis antes e após a introdução da hipotermia terapêutica em lactentes com encefalopatia hipóxica‐isquêmica (EHI). Método: Crianças nascidas entre 2003 e 2015 e diagnosticadas com espasmos infantis (espasmos epilépticos com ou sem hipsarritmia) nos primeiros 2 anos de vida foram identificadas por meio de checagem dos relatórios de eletroencefalografia e listas de pacientes de neurologia pediátrica. Dados sobre nascidos vivos foram obtidos nas bases de dados estatísticas dos hospitais regionais. Prontuários médicos sobre casos de espasmos infantis foram revisados quanto a dados demográficos, resultados diagnósticos, resposta ao tratamento, curso da doença, e resultado desenvolvimental. Resultados: Quarenta e dois lactentes com espasmos infantis foram identificados. A incidência cumulativa de espasmos infantis até os dois anos de idade foi 4, 01 por 10.000 nascidos vidos. Diferenças devida ao sexo foram mínimas (22 meninos, 20 meninas) e a maior parte dos lactentes nasceu próximo ao termo, com idades gestacionais variando de 30, 0 41, 8 semanas (mediana [intervalo interquartil] 39, 6 sem [38, 1–40, 0sem]). A etiologia dos espasmos infantis foi identificada em dois terços dos casos, com a EHI sendo a causa mais comum (7 em cada 42). Outras causas incluíram anormalidades cromossômicas e monogenéticas (8 em 42). Os espasmos infantis aconteceram em graus moderados a severos de EHI, com incidência significantemente maior naqueles com EHI severa ( p =0, 029). Lactentes com EHI severa que não receberam hipotermia terapêutica tinham seis vezes mais probabilidade de desenvolver espasmos infantis comparados com os que receberam, mas a diferença não foi estatisticamente significativa. (4 em16 vs 1 em 24, p =0, 138). Interpretação: Este esudo fornece informação detalhada sobre espasmos infantis antes e após a introdução de hipotermia terapêutica. A severidade da EHI é um fator de risco para o desenvolvimento de espasmos infantis. A introdução de hiportermia terapêutica por ter tido um impacto, mas o efeito foi difícil de assegurar nesta coorte devido ao pequeno número de lactentes.